Diffusion Monte Carlo simulations of the dipole-bound state of the water dimer anion - Clary, D; Benoit, D (1999)
It is shown how the diffusion quantum Monte Carlo method for solving the Schrödinger equation can be adapted to calculate the lowest energy state of a dipole-bound cluster anion. Specifically, the method can be used to calculate the rotationally adiabatic potential curve that arises due to the interaction of an electron with a dipolar molecular cluster. The theory allows the motion of each monomer molecule to be coupled explicitly with the angular motion of the electron. Application is made to the anion of the water dimer. The method gives a clear picture of the reorientation of the monomer water molecules that produces an overall dipole moment for the water dimer that is favorable for forming a dipole-bound state with the electron. © 1999 American Institute of Physics.